Stereotactic body radiation therapy in the treatment of oligometastatic prostate cancer - Ahmed, Kamran A.; Barney, Brandon M.; Davis, Brian J.; Park, Sean S.; Kwon, Eugene D.; Olivier, Kenneth R. (Frontiers in Oncology, 2013)
Purpose/Objective(s): To report outcomes and toxicity for patients with oligometastatic (≤5 lesions) prostate cancer (PCa) treated with stereotactic body radiotherapy (SBRT). Materials/Methods: Seventeen men with 21 PCa lesions were treated with SBRT between February 2009 and November 2011. All patients had a detectable prostate-specific antigen (PSA) at the time of SBRT, and 11 patients (65%) had hormone-refractory (HR) disease. Treatment sites included bone (n=19), lymph nodes (n=1), and liver (n=1). For patients with bone lesions, the median dose was 20 Gy (range, 8-24 Gy) in a single fraction (range, 1-3). All but two patients received some form of anti-androgen therapy after completing SBRT. Results: Local control (LC) was 100%, and the PSA nadir was undetectable in 9 (53%) patients. The first post-SBRT PSA was lower than pre-treatment levels in 15 patients (88%), and continued to decline or remain undetectable in 12 patients (71%) at a median follow-up of 6 months (range, 2-24 months). Median PSA measurements before SBRT and at last follow-up were 2.1 ng/dl (range, 0.13 – 36.4) and 0.17 ng/dl (range, <0.1- 140), respectively. Six (55%) of the 11 patients with HR PCa achieved either undetectable or declining PSA at a median follow-up of 4.8 months (range, 2.2-6.0 months). Reported toxicities included one case each of grade 2 dyspnea and back pain, there were no cases of grade ≥3 toxicity following treatment. Conclusion: We report excellent LC with SBRT in oligometastatic PCa. More importantly, over half the patients achieved an undetectable PSA after SBRT. Further follow-up is necessary to assess the long-term impact of SBRT on local control, toxicity, PSA response, and clinical outcomes.